Perkembangan Pariwisata di Banyuwangi Pada Tahun 2000-2015 - Al Jundi, Fauzan; *, Sulandjari; Dewi Setiowati Sunaryo, Fransiska (Humanis, 2017)
Banyuwangi is an area which newly growth as tourism destination. As the area called The Sunrise of Java, Banyuwangi started to focus its attention to tourism industry. Tourism in Banyuwangi begun with validity of regional autonomy, this was the main step of growing and handling many assets or the potential of Banyuwangi to concerns regional economic development. The government of Banyuwangi already makes plan to build Banyuwangi from many sector, and one of the sector is tourism’s sector.
Keywords: Social change, Development of tourism, The effect on society.